Observer Based Output Feedback Control of Thrust Magnetic Bearings - Okur, Beytullah; Zergeroglu, Erkan; Tatlicioglu, Enver; Basaran, Sinan; Sivrioglu, Selim (IEEE, 2011)
In this paper, we present an observer based output feedback controller for a thrust magnetic bearing system. A model independent variable structure like observer is used to determine the rotor velocity in order to remove the velocity dependency of the controller. The desired system dynamics have been utilized in the controller design and asymptotic stability of the observer-controller couple is guaranteed via Lyapunov based arguments. Experimental results are presented to illustrate the performance and feasibility of the proposed method.
Keywords: TRACKING CONTROL; Automation & Control Systems